P-057 Harvey-Bradshaw Index Captures Clinical Efficacy of Vedolizumab Induction Therapy for Active Crohn's Disease. (March 2016) - Abramowitz, Meira; Dale, Marissa; Saumoy, Monica; Schneider, Yecheskel; Feder, Scott; Scherl, Ellen; Longman, Randy
Abstract : Background: Vedolizumab, a humanized monoclonal antibody that specifically recognizes the α4β7 integrin, is currently indicated for achieving clinical response and remission in adult patients with moderately to severely active Crohn's disease (CD). Recent results from the GEMINI 2 trial revealed the efficacy of vedolizumab in inducing and maintaining remission (CDAI <150), but not clinical response (CDAI-100) at week 6 and week 52. Subsequent analysis of patients who failed anti-TNFα treatment (GEMINI 3) revealed statistically significant changes in CDAI-100 at weeks 6 and 10. Validation of these data are difficult given the cumbersome nature of CDAI recording in clinical practice. The Harvey-Bradshaw Index (HBI), which correlates strongly with CDAI, provides a clinically validated disease activity score that allows physicians to rapidly capture disease activity index in a clinical setting; however data evaluating the efficacy of the HBI in capturing clinical response in CD is limited. The aim of this study is to use the HBI to evaluate the clinical efficacy of vedolizumab in moderate to severe Crohn's patients following induction therapy. Methods: A retrospective cohort analysis was conducted in moderate to severe CD patients treated with vedolizumab at the Jill Roberts Center for IBD at Weill Cornell Medical College from July 2014 through May 2015. Vedolizumab induction therapy was administered at 0, 2, and 6 weeks. HBI was recorded at week 0 and at the first post-induction visit (week 10 or 14) to assess clinical efficacy. Clinical response was defined as a decrease in the HBI ≥3 and clinical remission as HBI ⩽4. Results: Thirty patients were included in the study (47% male, average disease duration 17.5 years). The majority of patients, 83%, were anti-TNFα failures. At the first post-induction visit, 60% (18/30) and 37% (11/30), achieved clinical response and clinical remission with an average decrease in HBI of 3.7 ( P = 0.0001). No significant decreases in the HBI subscore of extra-intestinal complications (53% versus 43%, P = 0.2) or ESR and CRP were observed in the first post-induction visit (ESR 26.5 versus 22.6, P = 0.53; CRP 2.48 versus 3.28, P = 0.54) suggesting potential discordance with extra-intestinal manifestations and conventional systemic biomarkers. Conclusions: These data support the efficacy of vedolizumab in anti-TNFα experienced patients and suggest that HBI is an effective clinical disease index to use in monitoring improvement following vedolizumab induction therapy.